DETERMINING THE DEGREE OF HISTORICAL CONSCIOUSNESS AMONG PRIMARY SCHOOL TEACHER EDUCATION COLLEGE STUDENTS STUDYING HISTORY IN RELATION TO ETHNICITY - Wanda, Karina; Ghufron, Anik; Syamsi, Ibnu (SENSEI RESEARCH CENTER, 2023)
This study set out to determine the degree of historical awareness among Indonesian college students about various ethnic groups, with a focus on Melayu and Batak ethnic groups. The four components of historical awareness are knowledge of historical events, comprehension of historical research techniques, interpretation of historical events, and historical utility perception. The subjects of this study were college students from two different universities: State University of Medan, which represented Melayu students studying history education, and University of Sumatera, which represented Batak students studying history education. Through the use of a historical consciousness exam, research data were gathered. Multiple-choice questions were developed as test instruments, which assessed knowledge of historical events, comprehension of historical research methodologies, and interpreting historical events, as well as considering the value of history. The proportion of the average historical consciousness scores for each ethnic group of college students was used to examine the data. Overall, the analysis of the results revealed that Melayu college students scored 42% higher on the historical consciousness scale than Batak college students, who scored 39%. This indicates that Melayu college students have a greater level of historical consciousness than Batak college students. The T-test result indicates that there was no significant difference in the historical consciousness of Melayu college students and Minang (df = 78, value sig. 0.198 < 0.08). One may argue that Melayu college students have the same amount of historical awareness as Minang students.